Take control of Zoom (2.1) - Fleishman, Glenn (Take Control Books, 2022)
Take your videoconferencing skills from zero to Zoom! Version 2.1, updated January 31, 2022 The rise of Zoom during the pandemic has made many of us comfortable with this popular videoconferencing software. But the differences in Zoom from one platform to the next, the long list of complex features, and a constant stream of updates make it challenging to master. Take Control of Zoom, Second Edition provides a comprehensive look at Zoom from start to finish. Beginners will learn everything they need to get started, while more advanced users will sharpen their skills and discover new tricks. Everyone will benefit from extensive details on privacy and security. Many of us rarely touched a video chat or videoconferencing tool until the pandemic hit. Now, we videoconference daily (or more often) for all sorts of reasons--we've gone from zero to Zoom! Despite Zoom's broad adoption, users sometimes struggle to keep up with its features and interface. Zoom changes constantly, and often spreads useful features across several places. This new edition of the book covers all the latest changes and the differences among platforms. You'll learn which Zoom app to use, how to configure your account and app even before your first meeting, how to work in Zoom views and chat in a meeting, and how to create and manage your own meetings. The book also covers how to share your screen, make presentations with PowerPoint or Keynote, annotate shared images, record audio and video, use full-screen mode and multiple displays, and work with machine-learning transcription and captioning. You also learn about virtual cameras--software like Camo, mmHmm, OBS, and Zoom's built-in Slides as Virtual Background feature--that can take one or more media sources--still images, video, animation, app windows, and sometimes more--and mix into a camera feed you can simply select and broadcast as a host or participant in Zoom. This book provides comprehensive advice and directions on planning a meeting, starting it up, and managing it, including running polls and setting up and using breakout rooms. It also provides extensive insight into keeping meetings safe, and warning or removing problematic participants. But what about privacy and security? Since early 2020, Zoom has fixed bugs, promised improvements and delivered them, and come clean about where it fell short. The book covers the current state of Zoom security and privacy, including an end-to-end encryption (E2EE) preview available to all hosts. You can find out how E2EE works, Zoom's implementation of it, how to enable it, and how to make sure your E2EE session remains free of snoopers. Topics include: How to install and configure Zoom Choosing whether or when to use the Zoom web app Configuring your physical setup and hardware for best audio and video quality Mastering meeting participation, including the various methods of "speaking up" Zoom's many mobile and desktop views for seeing other people and shared screens The best ways to present using PowerPoint and Keynote Finding the best combination of screens and devices to manage each of your presentations Becoming a host and starting meetings with one other person or 1,000 Conducting polls and managing breakout rooms Using automatic transcription and captioning features How to preserve your privacy when sharing apps, presentations, or other parts of your screen Recording a meeting for later playback, presentation, or a podcast Deciding whether to upgrade to a paid Zoom tier for meetings you host Zoom's security options, including end-to-end encryption How co-host and alternate host roles work in managing a meeting.